PENGARUH LITERASI PAJAK, TRANSPARNSI PAJAK, DAN PENERAPAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KABUPATEN MUSI BANYUASIN (Survey Pada KPP Pratama Sekayu, Kecamatan Sekayu) - Fina Aberta; Lili Syafitri; Mutiara Kemala Ratu (JURNAL ILMIAH EDUNOMIKA, 2026)
Taxpayer compliance is a crucial factor in supporting state revenue, but it is still influenced by tax understanding, trust in the tax system, and ease of administrative services. This study aims to analyze the influence of tax literacy, tax transparency, and the implementation of e-filing on individual taxpayer compliance in Musi Banyuasin Regency (survey at the Sekayu Pratama Tax Office). The study used a quantitative approach with a survey method by distributing questionnaires to 100 respondents. The data obtained were analyzed using multiple linear regression with the help of SPSS version 27.0. The results show that tax literacy, tax transparency, and the implementation of e-filing, both partially and simultaneously, have a significant effect on individual taxpayer compliance. This finding indicates that the better the level of tax understanding, the transparency of tax information, and the ease of use of the e-filing system, the higher the level of taxpayer compliance. Therefore, improving tax compliance requires integrated efforts through continuous tax education, increasing the transparency of tax policies, and optimizing digital services to create an effective, efficient, and reliable tax system. Keywords : Tax Literacy, Tax Transparency, Implementation of e-filing, Individual Taxpayer Compliance